Federated States of Micronesia : Selected Issues and Statistical Appendix. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2005)
This Selected Issues paper on the Federated States of Micronesia (FSM) underlies economic development. Since independence, the FSM has been heavily dependent on assistance from the United States. With government expenditure of more than 60 percent of GDP, the private sector remains underdeveloped, functioning largely as a provider of services to the public sector. Under a comprehensive reform scenario, further budgetary efforts are to be taken, as well as structural reforms. Given the need for fiscal consolidation, tax reform has been the subject of discussion for a number of years, although with little progress to show.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet